Pembangunan sistem nyah cemar kimia anggota untuk tentera darat Malaysia - Tan, Meng Loon (2006)
Disputes and unstable status of todays world must be tackled wisely and as those irresponsible parties may decide to use chemical weapons as their option. This matter should be in top priority as the number of the terrorist attacks keep increasing from time to time and the technology knowledge of terrorist should not be look down upon. Chemical decontamination is a process of cleaning the protective clothings and equipments that had been used by a soldier after he or she had gone into a contaminated area for carrying out their duty. A suitable chemical decontamination system for the Malaysian Army is very vital for the success of a mission. In this project a suitable chemical decontamination system had been developed for the Malaysian Army and this system can be used any where in Malaysia. The development process of this system is customised to suit the Malaysian Army’s needs and its framework is suggested to be used for all the development projects that will be involving the military in Malaysia. The chemical decontamination technology is still young in this region and it is a very vital technology for any countries to develop themselves for their own defence purposes.